Prescribing statin therapy in physically (in)active individuals vs prescribing physical activity in statin-treated patients: A four-scenario practical approach - Blanca Gavilán-Carrera; Alberto Soriano-Maldonado; Juan Diego Mediavilla-García; Carl J. Lavie; José Antonio Vargas-Hitos (Elsevier, 2023)
Statins are among the most commonly prescribed medications worldwide. Statin-associated muscle symptoms (SAMS) represent a frequent statin-related adverse effect associated with statin discontinuation and increased cardiovascular disease (CVD) events. Emerging evidence indicate that the majority of SAMS might not be actually caused by statins, and the nocebo/drucebo effect (i.e. adverse effects caused by negative expectations) might also explain SAMS. Physical activity (PA) is a cornerstone in the management of CVD risk. However, evidence of increased creatine-kinase levels in statin-treated athletes exposed to a marathon has been generalized, at least to some extent, to the general population and other types of PA. This generalization is likely inappropriate and might induce fear around PA in statin users. In addition, the guidelines for lipid management focus on aerobic PA while the potential of reducing sedentary behavior and undertaking resistance training have been overlooked. The aim of this report is to provide a novel proposal for the concurrent prescription of statin therapy and PA addressing the most common and clinically relevant scenarios by simultaneously considering the different stages of statin therapy and the history of PA. These scenarios include i) statin therapy initiation in physically inactive patients, ii) PA/exercise initiation in statin-treated patients, iii) statin therapy initiation in physically active patients, and iv) statin therapy in athletes and very active individuals performing SAMS-risky activities.